Pachydermodactyly - Ana C. Fernandes; Cristina Amaro; Luís Gargaté; João Maia-Silva (Publicaciones Permanyer, 2023)
A 14-year-old boy with a history of atopy went to the dermatologist with a history of progressive painless swelling of the fingers on both hands in the last two years. Manifestations of systemic or mental disorders were excluded.